2019
DOI: 10.1089/ars.2018.7517
|View full text |Cite|
|
Sign up to set email alerts
|

Protection of Kidney Function with Human Antioxidation Protein α1-Microglobulin in a Mouse 177Lu-DOTATATE Radiation Therapy Model

Abstract: We describe nephroprotective effects of human recombinant A1M on the short- and long-term renal damage observed following lutetium 177 (Lu)-DOTATATE (150 MBq) exposure in BALB/c mice. After 1, 4, and 8 days (short term), Lu-DOTATATE injections resulted in increased formation of DNA double-strand breaks in the renal cortex, upregulated expression of apoptosis and stress response-related genes, and proteinuria (albumin in urine), all of which were significantly suppressed by coadministration of A1M (7 mg/kg). Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 34 publications
3
38
1
Order By: Relevance
“…It was recently shown that coadministration with rA1M could inhibit renal damage in non-tumor-bearing mice up to 6 mo after injection of 150 MBq of 177 Lu-octreotate (15). In the present study, we found that coadministration with rA1M did not prevent Figure 2.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…It was recently shown that coadministration with rA1M could inhibit renal damage in non-tumor-bearing mice up to 6 mo after injection of 150 MBq of 177 Lu-octreotate (15). In the present study, we found that coadministration with rA1M did not prevent Figure 2.…”
Section: Discussioncontrasting
confidence: 59%
“…rA1M, with its antioxidation properties and its similar biodistribution and pharmacokinetics to that of the 111 In-labeled somatostatin analog octreotide (14), is an interesting candidate for renal protection during treatment with 177 Lu-octreotate. Inhibition of renal damage by coadministration with rA1M has recently been studied in non-tumor-bearing mice up to 6 mo after injection of 150 MBq of 177 Lu-octreotate (15). The results indicate that rA1M could potentially protect kidney tissue from radiation-induced damage, allowing for reduced toxicity or dose escalation.…”
mentioning
confidence: 99%
“…In a mouse model of radiation therapy, co-injection of A1M resulted in increased long-term survival and reduced histological and functional renal damage. In the short-term, the mice that received A1M had less DNA damage and upregulation of apoptotic genes in the kidneys [ 59 ]. In a follow-up study, it was confirmed that A1M did not interfere with tumor treatment or with the biodistribution of the radiopeptides [ 60 ].…”
Section: A1mmentioning
confidence: 99%
“…Acute and hyperhemolytic episodes are associated with renal damage, which may be temporary or permanent. It has been shown previously that A1M can protect against renal damage following radiation treatment and rhabdomyolysis [ 59 , 60 ]; however, its protective role during active RBC hemolysis is not clear, and Ofori-Acquah et al have shown a correlation between kidney damage and increased A1M-bound heme in sickle cell disease [ 62 , 63 ]. Thus, the role of A1M protection in hemolytic transfusion reactions needs to be examined further ( Figure 5 ).…”
Section: Hemolytic Conditionsmentioning
confidence: 99%
“…Furthermore, the use of γ-H2AX detection for quantification of irradiation effects from acute single or split exposure by external beam irradiation within various cells in vitro [6,7] and in tissues after in vivo irradiation [8][9][10][11] has been reported. However, studies on the presence of γ-H2AX foci after continuous internal irradiation after systemic administration of radiopharmaceuticals used for therapy have been confined to leukocytes in the peripheral blood cells [12,13] and mice kidneys [14]. Hence, it is currently unclear how DNA DSBs are distributed within differentiated mammalian tissue after internal irradiation originating from radionuclides or radiopharmaceuticals and how different tissues within normal organs respond.…”
Section: Introductionmentioning
confidence: 99%